The Effect of a 18-Week Supervised Exercise Program on Changes in Weight and Health Status in Overweight Individuals: The Healthy Weight Beginner and Intermediate Program - Pholi, Kuda Nozibelo Grace (Department of Human Biology, 2023)
Background: According to the South African National Health and Nutrition Examination Survey, approximately 69% of South African women and 29% of men are considered overweight/obese. In South Africa, overweight and obesity rates are on the rise and have reached epidemic proportions. Several conventional weight loss strategies have been employed and have been unsuccessful in addressing this issue. It is for this reason that this study strives to uncover if any improvement in weight and fitness status are associated with an improvement in health status. Methods: One of our main aims were to determine the success in weight loss and reduction in health risk factors in members who have completed 18-weeks of the Healthy weight programme. Therefore, this study is a retrospective, observational study of adults with a mean body mass index (BMI) of 32.63 ± 7.39 who completed an 18-week supervised exercise program. An online health questionnaire was completed followed by pre- intervention assessments which included: Anthropometric measures (height, weight, waist circumference, body fat percentage) followed by blood pressure, finger-prick random glucose and cholesterol measurements. A 12-min motion test to assess functional capacity were completed. All anthropometric, resting health measures and fitness tests were repeated at 12-weeks (post-beginner programme) and 18 weeks (post-intervention) after the start of the intervention. The intervention included 2 weekly classes with an optional gym class. The type of exercise intervention that was included in this study largely focused resistance training and cardiorespiratory fitness which targeted multiple large muscle groups. Each exercise session included 80 to 90 % exercise intensity as well as lumbopelvic core exercises. The data set was analysed as an intention to treat (ITT) protocol as some of the testing time points were missing. Results: Out of a possible 50 participants, 34 met the inclusion criteria of at least all 3 health measures taken on the 3 different occasions (baseline, post-beginner, postintervention). The 34 participants had a mean age of 47.26 ± 10.44 ranging between 24 years and 76 years old. 65 % of the participants were female. Anthropometric results showed significant changes in weight and waist circumference at 12- and at 18-weeks compared to baseline measures (p < 0.005). Additionally, body fat % significantly reduced at 12-weeks but increased slightly at 18 weeks diminishing the significant reduction compared to the baseline measure. In terms of fitness, participants succeeded in improving their average distance to complete a 12-min motion test by 14.5% (p < 0.001) at 12-weeks and 20% (p < 0.001) at 18-weeks compared to starting measures, respectively. After adjusting for multiple comparisons during post-hoc analysis, none of the health status outcomes (blood pressure, random glucose, random cholesterol) showed a significant improvement at any of the time points. In terms of associations, a change in body fat % could significantly explain some of the variance in the change (from baseline to 18-weeks) in cholesterol; and a change in weight could significantly explain some of the variance in the change in glucose over the same intervention time. Conclusion: The results of this study revealed the 18-week supervised exercise intervention led to a modest reduction (approximately 5%) in weight and a substantial improvement in fitness. However, no changes in health status were observed, suggesting that greater improvements in weight and fitness may be required to have a profound influence on health status.